How food marketers can sell smaller portions: Consumer insights and product innovation. (1st August 2016) - Riis, J.; Fisher, J.O.; Rowe, S.
Abstract: Food portion size has been shown to be an important driver of energy intake. Despite the well acknowledged role of portion control in weight management, large portion sizes remain ubiquitous in the marketplace. Moving consumers towards consumption of smaller portion sizes will require changes in consumer behavior as well as changes in products available to consumers in a variety of settings. This special supplement presents cutting edge research aimed at understanding consumer behavior around portion size and innovations in product design that may promote the selection and consumption of smaller portion sizes. We identify further research that will be needed to translate basic behavioral findings into real world settings and to viable product development.